α-Amylase immobilization on gelatin: Optimization of process variables - Jaiswal N.; Prakash O.; Talat M.; Hasan S.H.; Pandey R.K. (My University, 2025)
α-Amylase was extracted and purified from soybean seeds to apparent homogeneity by affinity precipitation. The homogeneous enzyme preparation was immobilized on gelatin matrix using glutaraldehyde as an organic hardener. Response surface methodology (RSM) and 3-level-3-factor Box-Behnken design was employed to evaluate the effects of immobilization parameters, such as gelatin concentration, glutaraldehyde concentration and hardening time on the activity of immobilized α-amylase. The results showed that 20% gelatin (w/v), 10% glutaraldehyde (v/v) and 1 h hardening time yielded an optimum immobilization of 82.5%. © 2012 Academy of Scientific Research and Technology.